PERANCANGAN SISTEM INFORMASI KUNJUNGAN PASIEN RAWAT JALAN BERBASIS WEB - Fiqri, Arijalul; Syahidin, Yuda; Hidayati, Meira (STMIK Palangkaraya, 2022)
The design of an outpatient visit information system is a form of need for the hospital system which is believed to provide convenience for medical record officers in analyzing outpatient visit data. I hope that with the outpatient information system it can be easier to access data and store data. The outpatient visit system is not computerized and officers need to re-enter visit data to manage patient visit data and this is quite time-consuming which causes the information produced to be slow, less accurate and irrelevant. For this reason, researchers evaluate the existing work system at the hospital order to improve good system governance. Researchers use Microsoft Visual Studio 2010 determining the program. The results in this system are that initial introduction to prospective system users, a performance evaluation is carried out to anticipate changes information needs the future and is more thorough in lending and storing medical record files.